Μ-Oxo-bis[(octacosafluoro-meso-tetraphenylporphyrinato)iron(iii)] – synthesis, crystal structure, and catalytic activity in oxidation reactions. Issue 2 (15th December 2022) - Schuh, Tristan; Kataeva, Olga; Knölker, Hans-Joachim
Abstract : We describe the synthesis and crystal structure of a novel perfluorinated μ-oxo-bis[(porphyrinato)iron(iii )] complex enabling useful applications in catalytic C–H activations including asymmetric biaryl coupling and Wacker-type oxidation of olefins. Abstract : We describe the synthesis and X-ray crystal structure of μ - oxo-bis[(octacosafluoro- meso -tetraphenylporphyrinato)iron(iii )] [(FeTPPF28 )2 O]. This novel iron complex is an efficient catalyst for oxidative biaryl coupling reactions of diarylamines and carbazoles. The asymmetric oxidative coupling in the presence of an axially chiral biaryl phosphoric acid as co-catalyst provides the 2, 2′-bis(arylamino)-1, 1′-biaryl in 96% ee . The Wacker-type oxidation of alkenes to the corresponding ketones with (FeTPPF28 )2 O as catalyst in the presence of phenylsilane proceeds at room temperature with air as the terminal oxidant. For internal and aliphatic alkenes increased ketone/alcohol product ratios were obtained.